Engaging Learners through Authentic Listening Materials - Rustamova, Sevinch (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study explored the impact of using authentic materials on students’ listening comprehension in an EFL classroom context. Using a quantitative experimental design with pre-tests and post-tests, the findings revealed that students exposed to authentic listening materials achieved significantly higher scores and demonstrated greater engagement and motivation.